Evaluasi Risiko Implementasi Chatbot AI Pada Mobile Banking Bank XYZ Dengan Metode Octave Allegro - Fathin, Afif; Hadid; Angraini (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
The chatbot AI SALMAH is implemented in the Mobile Banking service of Bank XYZ Pekanbaru Branch to improve customer service based on Islamic banking principles. The system aims to provide instant, accurate, and syariah-compliant assistance to customers. However, several risks are associated with this AI integration, including data security, regulatory compliance, and user adoption challenges. This study aims to identify potential threats, evaluate risks, and analyze their impact on banking operations using the High-level IT Risk Assessment framework supported by concepts from OCTAVE Allegro. The assessment revealed five key risk factors: syariah regulatory compliance, data security, customer adoption, industry competition, and rapid technological change. Mitigation strategies include strengthening data protection, customer education, system updates, and continuous monitoring. The highest risk was related to data security breaches and inaccurate chatbot responses. This research provides valuable insights for managing IT risks in syariah-based digital banking services and guides further improvements in AI implementation. Future studies may focus on comprehensive mitigation measures and effectiveness monitoring.